Regional citrate anticoagulation for continuous renal replacement therapy in newborns - Huang, Haixia; Deng, Xing; Bai, Ke; Liu, Chengjun; Xu, Feng; Dang, Hongxing (Frontiers in Pediatrics, 2023)
Background Regional citrate anticoagulant (RCA) is recommended as the preferred anticoagulant regimen for continuous renal replacement therapy (CRRT) in adults; however, it is rarely reported in neonates due to concerns associated with their immature liver. Few studies have reported on the use of RCA to evaluate the safety and efficacy of RCA-CRRT in neonates. Method In this retrospective observational study, we reviewed the clinical records of neonates who underwent RCA-CRRT at our pediatric intensive care unit between September 2015 to January 2021. Results A total of 23 neonates underwent 57 sessions of RCA-CRRT. Their mean age was 10.1 ± 6.9 days and mean weight was 3.0 ± 0.7 kg (range, 0.95–4 kg). The mean filter life was 31.54 ± 19.58 h (range, 3.3–72.5 h). Compared to pretreatment values, the total-to-ionized calcium ratio (T/iCa) on RCA-CRRT increased (2.00 ± 34 0.36 vs. 2.19 ± 0.40, P = 0.056) as did the incidence of T/iCa levels >2.5 (11.4 vs. 14.3, P = 0.477), albeit not significantly. Using a post-treatment T/iCa threshold of 2.5, we divided all the cases into citrate accumulation (CA) and non-CA (NCA) groups. Compared with the NCA group, the CA group had significantly higher body weight (3.64 ± 0.32 kg vs. 2.95 ± 0.41 kg, P = 0.033) and significantly lower blood flow rate per body weight ml/kg/min (3.08 ± 0.08 vs. 4.07 ± 0.71, P = 0.027); however, there was no significant difference between the two groups in terms of age, corrected gestational age, the PRISM-III score, and biochemical tests. Conclusion RCA-CRRT is safe and effective for neonates. After appropriate adjustments of the RCA-CRRT parameters, the incidence of CA was not higher in neonates than in children or adults, and CA was not found to be significantly correlated with age or corrected gestational age.